The use of simulink block diagram to solve mathematical model and control equations - Ghasem, N.M.; Hussain, Mohd Azlan; Mujtaba, I.M. (Design and Technology, 2003)
In this paper, the simulink block diagram used to solve a model consists of a set of ordinary differential and algebraic equiations to control the temperature inside a simple stirred tank heater. The flexibility of simulink block diagram gives studens better understanding of a control systems. The simulink also solutions of mathematical models and easy visualizations of the system variables. A polyethylene fluidized bed reactor is considered as an industrial example and the effect of the Proportional, integral and Derivative contol policy is presented for comparison.